The first report on the phenomenon of Capoeta aydinensis (Cyprinidae), occurring in Gökova Bay, Aegean Sea - Hasan Sarı (Su Ürünleri Dergisi, 2020)
A big specimen of Capoeta aydinensis (435 mm TL, 1040 g) was caught on 22 March 2020 by an angler from the Gökova Bay, Muğla as an unusual habitat. This case report presents occurring of an endemic freshwater fish in the marine waters and this specimen has the maximum size throughout the Anatolia.